If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(7)-2y=1
We move all terms to the left:
(7)-2y-(1)=0
We add all the numbers together, and all the variables
-2y+6=0
We move all terms containing y to the left, all other terms to the right
-2y=-6
y=-6/-2
y=+3
| 4x-8=-(9-4x) | | t/0.25+3=15 | | 15+7.1n=10+7.3n | | .75/x/4=1 | | 3(2m)=6 | | -7(x-17)x=-35 | | n3=-216 | | -8x+4=-6x+24−6x+24 | | 14,2w-2.1=97.3 | | 7n+–5+–=4n+–7n | | -9x-9=5x-29 | | 0.5(x−6)=0.45(2x−12) | | R(w)=75-4.5w | | r-11.1=4.8 | | 55-(2c+3)=4(c+6) | | 3b^2=12b+63 | | 2x÷-3=2 | | 6(4y-9)=-42 | | -1-(5x-3)=-8x+20 | | x-9=36-2x | | (8x+3)^2-15(8x+3)-16=0 | | r-11.1/3=-1.6 | | x+9=36-2 | | 6t+-3=3t+6 | | w+7.835=9.701 | | 6y+4=4(6y-4) | | −(8x+6)=−8x−7 | | 2(k-13)-2=8 | | -3(-5x+8)=15x-25 | | 6y-10-3y+8=) | | 32(6x+9)=41(12x+8) | | (x+3)^3/2=343 |